Risk assessment in emerging equity markets: the case of South Africa - Sibanda, Donald (My University, 2014)
South Africa is gripped by a poor investment culture with a large number of adults not investing. There is need to inform would be investors about alternative forms of investments like the stock market. The research estimates the amount of risk exposure for a South African equity portfolio using Value at Risk (VaR). The research reviews literature to get an understanding of the commonly used risk measure for financial markets. It looks at pros and cons of using VaR in determining risk exposure for the financial markets. The research will explore all possible methods of calculating VaR these are namely; Historic simulation, Monte Carlo simulation and Variance covariance method. VaR for the purpose of this research is calculated using the variance covariance method An equity portfolio is constructed using PE ratio as cut off criteria (cut off range 10<PE<12), this made the size of the portfolio small (20 stocks that complied with the selection criteria). The research will give an estimate value of amount of exposure to be expected in an equity portfolio.